2018
DOI: 10.3329/jbcbm.v4i1.37876
|View full text |Cite
|
Sign up to set email alerts
|

Water quality assessment of the river Buriganga, Bangladesh

Abstract: The present investigation was conducted to assess the water quality status of the river Buriganga. Water samples were collected from three selected stations in wet (June-August) and dry (November-January) seasons during the years 2017 and 2018. Temperature and Dissolved Oxygen (DO) of water varied from 22.80 to 31.40 °C and 0.22 to 2.74 mg/L, respectively. Electrical conductivity of water varied from 180 to 598 μS/cm while pH ranged from 7.61 to 8.97. This study showed that temperature, DO and Fe were higher i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 3 publications
(6 reference statements)
2
11
0
Order By: Relevance
“…The lowest level of DO was obtained next to the Savar tannery area. The following DO criteria are permissible following the Environmental Quality Standard (EQS): Fish and domesticated animals need 4–6 mg/L; 6 mg/L for drinking, 4–5 mg/L for industrial purposes, and up to 5 mg/L for industrial applications ( 57 ). Organic chemicals released from sources such as wastewater treatment facilities, storm floods, slurry agriculture, and alcohol silage are possible explanations for the depleted dissolved oxygen levels in the water.…”
Section: Resultsmentioning
confidence: 99%
“…The lowest level of DO was obtained next to the Savar tannery area. The following DO criteria are permissible following the Environmental Quality Standard (EQS): Fish and domesticated animals need 4–6 mg/L; 6 mg/L for drinking, 4–5 mg/L for industrial purposes, and up to 5 mg/L for industrial applications ( 57 ). Organic chemicals released from sources such as wastewater treatment facilities, storm floods, slurry agriculture, and alcohol silage are possible explanations for the depleted dissolved oxygen levels in the water.…”
Section: Resultsmentioning
confidence: 99%
“…In each polypropylene bottle, 1 mL of ultrapure nitric acid was added to achieve a pH of ~1 [47] before transferring to the Department of Soil, Water and Environment Laboratory of the University of Dhaka for heavy metals analysis. The standard sampling procedure was followed to collect all samples at every single sampling station [48][49][50][51][52].…”
Section: Description Of the Study Area And River Water Samplingmentioning
confidence: 99%
“…Sampling station D-1 exhibited the lowest value of DO (0.06 mg/L) beside the Savar tannery area. According to the Environmental Quality Standard (EQS), the accompanying DO requirements are acceptable: fish and domesticated animals require 4 to 6 milligrams per liter and 6 mg/L for drinking, 4 to 5 milligrams per liter, whereas industrial applications require up to 5 milligrams per liter [50].…”
Section: Assessment Of Physicochemical Parameters Of Surface Watermentioning
confidence: 99%
“…The Buriganga river water is a threat to the contamination from untreated municipal wastes, industrial discharges, runoff from organic and inorganic fertilizers, and pesticide emission around the river and leading to the extinction of aquatic life and breakdown of the river ecosystems [43]. Fatema et al [44] found that the Buriganga river was highly polluted with heavy metals during the dry season, which is harmful to the river ecosystem. The results from the present study showed that heavy metal pollution in river water was not safe for living organisms.…”
Section: Water Quality Parameters During the Study Periodmentioning
confidence: 99%